Environmental Awareness Level Among University Students in Malaysia: A Review - Mohd Khairul Amri, Kamarudin; Syazni, Jusoh; Noorjima, Abd Wahab; Muhammad Hafiz, Md Saad (2018)
Environmental awareness is one concept to understand the fragility of our environment and importance of its protection. Environmental awareness program among university students have greatly improved over the years. However, environmental issues always arise as a disaster in the world. Therefore, the main objective of this study is to review the level of environmental awareness issue among universities students in Malaysia. The result showed the level of environmental awareness among university students had high level of knowledge but the level of practices was moderate. They are not applicants and practice this awareness in their life. Therefore, more effective initiatives need to be due by the authorities and the government to preserve our environment. The level of knowledge and practice of the environment care has greatly contributed to the environmental sustainability in Malaysia.